COPD: Recent Updates and Role of Chronic Disease Management and Protocolized Management. Issue 4 (July 2017) - Salman, Zafirah; Nobari, Matthew M.; Tybor, David; Khan, Babar A.; Diab, Khalil J.
Abstract : The annual cost of chronic obstructive pulmonary disease (COPD) in the United States in 2008 was 53.7 billion, largely due to visits to a medical facility for exacerbations. In this article, we explore the most recent updates on the medical management of COPD, including the most recently released inhalers. We also explore the role of COPD self-management and integrated disease management, and discuss the most recent studies pertaining to those. In addition, we discuss the most recent updates on bronchoscopic interventions for lung volume reduction. We also discuss the results of our study assessing the role of protocolized COPD management on the basis of Global Chronic Obstructive Lung Disease guidelines and its effects on COPD exacerbation rates, quality of life, and depression scores.